Performance Transformation in Health Sector: The Impact of Flexible Working Arrangement and Organizational Support on Centre for Health System Resilience Policy - Sulistyowati, Indah; Wibowo, Holy Arif; Oktoberia, Intan Sari; Zaharuddin, Zaharuddin; Budianto, Irawan R.D (International Journal of Business, Law, and Education, 2026)
ABSTRACT The COVID-19 pandemic accelerated the adoption of flexible working arrangements (FWA) in public institutions, yet evidence on whether such arrangements strengthen bureaucratic performance remains context-dependent. This study examines the effects of FWA and organizational support on employee performance at the Center for Health System Resilience Policy, Ministry of Health of the Republic of Indonesia. Using a quantitative cross-sectional design, data were collected from the full population of 56 employees through a structured questionnaire. The instrument measured FWA through time, timing, and place flexibility; organizational support through emotional, instrumental, informational, evaluative, and appreciative support; and employee performance through work quality, quantity, responsibility, cooperation, and initiative. The measurement model met validity and reliability criteria, and the regression diagnostics indicated normally distributed residuals, no heteroscedasticity, and no multicollinearity. The results show that FWA significantly predicts employee performance (B = 0.583, t = 2.332, p = 0.024), and organizational support also significantly predicts employee performance (B = 0.399, t = 3.390, p = 0.001). Simultaneously, both predictors explain 24.8% of the variance in employee performance (R = 0.525; adjusted R² = 0.248; F = 10.089, p < 0.001). These findings indicate that flexible work policies are more likely to improve performance when embedded in a supportive organizational system that provides clear guidance, adequate resources, and leadership support. The study contributes empirical evidence from an Indonesian public health policy institution and offers practical implications for designing adaptive, accountable, and performance-oriented work arrangements in the public sector.